Effects of selenium and iodine on Kashin-Beck disease: an updated review - Liu, Lin; Luo, Pan; Wen, Pengfei; Xu, Peng (Frontiers in Nutrition, 2024)
Kashin-Beck disease (KBD) is an endochondral osteogenesis disorder characterised by epiphysis damage and secondary deformable arthropathy induced by multiple external factors, among which selenium (Se) and iodine deficiency are important influencing factors. Iodine deficiency is usually accompanied by a low Se content in the soil in the KBD areas of China. Se can reverse oxidative damage to chondrocytes. In addition, Se is related to the bone conversion rate and bone mineral density. Low Se will hinder growth and change bone metabolism, resulting in a decrease in the bone conversion rate and bone mineral density. Thyroid hormone imbalance caused by thyroid dysfunction caused by iodine deficiency can damage bone homeostasis. Compared with Se deficiency alone, Se combined with iodine deficiency can reduce the activity of glutathione peroxidase more effectively, which increases the vulnerability of chondrocytes and other target cells to oxidative stress, resulting in chondrocyte death. Clinical studies have shown that supplementation with Se and iodine is helpful for the prevention and treatment of KBD.